2022
DOI: 10.1021/acs.jctc.1c01309
|View full text |Cite|
|
Sign up to set email alerts
|

Linear and Nonlinear Optical Properties from TDOMP2 Theory

Abstract: We present a derivation of real-time (RT) time-dependent orbital-optimized Møller–Plesset (TDOMP2) theory and its biorthogonal companion, time-dependent non-orthogonal OMP2 theory, starting from the time-dependent bivariational principle and a parametrization based on the exponential orbital-rotation operator formulation commonly used in the time-independent molecular electronic structure theory. We apply the TDOMP2 method to extract absorption spectra and frequency-dependent polarizabilities and first hyperpo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…The orbital-adaptive methods yield roughly the same intensity profiles as their static-orbital counterparts, but the transition frequencies are blue-shifted: ∼ 0.5 eV for TDOMP2 versus TDCC2 and ∼ 2 eV for OATDCCD versus TDCCSD. As has been observed previously [58], these blue-shifts are insignificant compared with other sources of error such as basis-set incompleteness and higher-order correlation effects. Electron-correlation effects are significantly more important than the orbital relaxation provided by dynamic orbitals, as seen in Fig.…”
Section: K Pre-edge Quadrupole Transitions In Tisupporting
confidence: 79%
See 2 more Smart Citations
“…The orbital-adaptive methods yield roughly the same intensity profiles as their static-orbital counterparts, but the transition frequencies are blue-shifted: ∼ 0.5 eV for TDOMP2 versus TDCC2 and ∼ 2 eV for OATDCCD versus TDCCSD. As has been observed previously [58], these blue-shifts are insignificant compared with other sources of error such as basis-set incompleteness and higher-order correlation effects. Electron-correlation effects are significantly more important than the orbital relaxation provided by dynamic orbitals, as seen in Fig.…”
Section: K Pre-edge Quadrupole Transitions In Tisupporting
confidence: 79%
“…The orbital expansion coefficients are either kept constant (static orbitals) at the groundstate Hartree-Fock (HF) level or allowed to vary in response to the external field (dynamic orbitals). Static orbitals are used in the time-dependent configuration interaction singles (TDCIS) [56], time-dependent secondorder approximate coupled-cluster singles-and-doubles (TDCC2) [57,58], and time-dependent coupled-cluster singles-and-doubles (TDCCSD) [59] methods. Dynamic orbitals are used in the time-dependent Hartree-Fock (TDHF) [56], time-dependent orbital-optimized secondorder Møller-Plesset (TDOMP2) [58,60], and orbitaladaptive time-dependent coupled-cluster doubles (OAT-DCCD) [61] methods.…”
Section: A Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach using biorthogonal orbitals (TDNOMP2) has been also reported and assessed for linear and nonlinear optical properties. 33 Although TD-OMP2 is based on the perturbation theory, it can be applied to high-field phenomena because the orbitals variationally evolve over time and the external field is totally included in the unperturbed Hamiltonian . is the permutation operator), which is significantly simpler than the original TD-OCCD equations of 𝑝 𝑝𝑞 motion.…”
Section: Time-dependent Optimized Coupled-cluster Methodsmentioning
confidence: 99%
“…However, for frequency‐dependent polarizabilities and hyperpolarizabilities extracted from TDCC2, TDCCSD, and TDOMP2 simulations with ramped monochromatic continuous‐wave lasers as suggested by Ding et al, 14 Kristiansen et al 98 found that TDOMP2 theory outperforms the TDCC2 model, producing linear and nonlinear response functions much closer to the full TDCCSD results. While the linear absorption spectra were in perfect agreement with results from linear response theory (to within the resolution of the Fourier transformation), the TDCC2 and TDCCSD polarizabilities and hyperpolarizabilities were found to deviate slightly.…”
Section: Electronic Dynamics With Bivariational CC Theoriesmentioning
confidence: 99%